A Systematic Analysis of Laboratory-Guided Diagnosis and Management of Covid-19: Challenges and Recommendations - Shane, Whelan; Daniel, Keaney; Brigid, Lucey; Karen, Finn (Journal of Diseases, 2020)
We conducted a comprehensive analysis of patient demographics and laboratory tests encompassing Real Time PCR (RT-qPCR) and serology for SARS-CoV-2 in addition to blood components and clinical blood markers for COVID-19 disease. All relevant literature was included up to 15 July 2020 and multiple studies were analysed in tandem to correlate findings. For RT-qPCR, nasopharyngeal swabs are the most suitable samples based on detection rates by sample, but may require repeat testing. One-week post-symptom onset, serological testing is a more stable marker. Antibody titers have been linked to disease severity. Several clinical blood components and markers have been reported to be prognostically useful; however, care is needed when making interpretation owing to the association between raised levels of these being found for the co-morbidities that predispose to worse prognosis in COVID-19. Challenges in the current study when finding the information presented in this paper suggest the need for a quality assured database that outlines the complete set of results, anonymised patient data for each entry and a set of internationally-agreed guidelines for complete laboratory testing, documentation and open-access reporting. We suggest that such information would be useful to help with patient diagnosis and management, worldwide.